Sulforaphane is superior than glucoraphanin in modulating carcinogen-metabolising enzymes in Hep G2 cells - Abdull Razis, Ahmad Faizal; Mohd Noor, Noramaliza (Asian Pacific Organization for Cancer Prevetion, 2013)
Glucoraphanin is the main glucosinolate found in broccoli and other cruciferous vegetables (Brassicaceae). The objective of the study was to evaluate whether glucoraphanin and its breakdown product sulforaphane, are potent modulators of various phase I and phase II enzymes involved in carcinogen-metabolising enzyme systems in vitro. The glucosinolate glucoraphanin was isolated from cruciferous vegetables and exposed to human hepatoma cell line HepG2 at various concentrations (0-25 μM) for 24 hours. Glucoraphanin at higher concentration (25 μM) decreased dealkylation of methoxyresorufin, a marker for cytochrome P4501 activity; supplementation of the incubation medium with myrosinase (0.018 U), the enzyme that converts glucosinolate to its corresponding isothiocyanate, showed minimal induction in this enzyme activity at concentration 10 μM. Quinone reductase and glutathione S-transferase activities were unaffected by this glucosinolate; however, supplementation of the incubation medium with myrosinase elevated quinone reductase activity. It may be inferred that the breakdown product of glucoraphanin, in this case sulforaphane, is superior than its precursor in modulating carcinogen- metabolising enzyme systems in vitro and this is likely to impact on the chemopreventive activity linked to cruciferous vegetable consumption.